Enhancing encapsulation efficiency of food-grade double emulsions containing resveratrol or vitamin B12 by membrane emulsification. (December 2015) - Matos, M.; Gutiérrez, G.; Iglesias, O.; Coca, J.; Pazos, C.
Graphical abstract: Highlights: Food-grade W1 /O/W2 emulsions containing resveratrol or vitamin B12 were prepared. Conventional and membrane emulsification (ME) techniques were used and compared. ME allowed to obtain uniform droplets with better barrier properties. Encapsulation efficiency for both bioactive compounds was considerably higher for ME. W1 /O/W2 emulsions exhibited viscoelastic behaviour with no destabilization phenomena. Abstract: Monodisperse food-grade water-in-oil-in-water (W1 /O/W2 ) double emulsions containing either trans -resveratrol (RSV) or vitamin B12 were prepared with high encapsulation efficiencies. Two techniques were employed: Conventional and membrane emulsification (ME). Encapsulation efficiency (EE) and storage release with time were determined. The emulsions were characterized by droplet size distribution, stability (by Turbiscan analysis) and rheological behaviour. EE was determined by RP-HPLC using UV–vis and fluorescence detectors. Mechanical agitation leads to polydisperse emulsions, while ME gives emulsions with uniform droplets of 59.82 ± 0.21 μm controlled mean size and span values in the range of 0.87–0.90. The EE for both bioactive compounds was considerably higher with ME, resulting in an initial increase of 24.7% for W1 /O/W2 double emulsions containing RSV and of 8% for emulsions containing vitamin B12 . Droplet size control by ME and appropriate formulation parameters are major factors for a successful production of functional foods with specific rheological behaviour for a wide range of applications.